Efektivitas Media Gambar Dalam meningkatkan Kemampuan Berhitung Permulaan Pada Anak Usia 5-6 Tahun di TK Afdonal Padanglawas - Hesi Kartikasari Harahap; Elva Wardani Harahap; Hasanah Hasanah (LPPI Yayasan Almahmudi bin Dahlan, 2023)
One of the very important abilities for children that needs to be developed in order to equip them for life in the future and now is to provide them with the ability to count. Thus, the aim of this research is to improve the beginning numeracy skills of children aged 5-6 years through Image Media at Afdonal Padanglawas Kindergarten. This research was carried out in two cycles and each cycle held two meetings. This research was carried out at Afdonal Padanglawas Kindergarten with research subjects being Group B aged 5-6 years, totaling 28 people. Data collection in this research used observation and documentation techniques. The results of the research were that in cycle 1, 25% of children were in the Not Yet Developed category and in cycle II it was 5%. Furthermore, in cycle 1, 45% of children were in the Starting to Develop category, while in cycle II it was 25%. Switching to the Developing According to Expectations category in cycle 1, 25% of children were in this category, whereas after cycle II it increased to 55%. Lastly, in the Very Well Developed category in cycle 1 it was only 5%, whereas after cycle II it increased to 15%. A follow-up to the results of this research is that image media is not only used for initial numeracy learning, but can also be used in other learning to optimize aspects of children's overall development. Keywords: Beginning Numeracy, Image Media, ECE